2021
DOI: 10.1016/j.ejca.2021.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin/capecitabine or carboplatin/paclitaxel-based preoperative chemoradiation for resectable oesophageal adenocarcinoma (NeoSCOPE): Long-term results of a randomised controlled trial

Abstract: This is the first randomised study to evaluate toxicity and survival outcomes of two neoadjuvant chemoradiotherapy (CRT) regimens for patients with localised oesophageal adenocarcinoma (OAC) or gastro-oesophageal junction (GOJ) adenocarcinoma. The initial results showed comparable toxicity between regimens and pathological complete response (pCR) rate favouring CarPacRT. Herein, we report survival, progression patterns, and long-term toxicity after a median follow-up of 40.7 months. Methods: NeoSCOPE was an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Patients in both arms additionally received two cycles of induction chemotherapy. In this phase II trial, improved overall survival in the carboplatin and paclitaxel arm was observed (HR 0.48, 95% CI 0.24–0.95, p = 0.035) [ 10 ], underlining the validity of the CROSS regimen. In contrast to the CROSS trial, women demonstrated significantly worse overall survival ( Table 1 ) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients in both arms additionally received two cycles of induction chemotherapy. In this phase II trial, improved overall survival in the carboplatin and paclitaxel arm was observed (HR 0.48, 95% CI 0.24–0.95, p = 0.035) [ 10 ], underlining the validity of the CROSS regimen. In contrast to the CROSS trial, women demonstrated significantly worse overall survival ( Table 1 ) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst this is somewhat supported by the improved outcomes seen with a similar FOLFOX regimen for patients receiving dCRT for OAC in the CALGB80803 trial, long-term data from the NeoSCOPE trial suggest superior overall survival with car/pac compared with oxaliplatin and capecitabine in patients receiving neoadjuvant CRT for OAC. 19 , 36 However, it should be noted that in ART-DECO (OSCC 61%, 39% OAC), a dCRT trial which used car/pac as systemic, survival was lower than SCOPE1 which used cis/cap regimen therapy (3 year OS ∼40% vs ∼50%). 22 These data do suggest that the use of cis/cap may be superior, at least when compared with a switch to car/pac, particularly in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Seven RCTs evaluated neoadjuvant chemoradiation compared to induction chemotherapy and chemoradiation [ 34 , 43 , 44 , 45 , 46 , 47 , 48 ]. One RCT evaluated intratumoral paclitaxel in addition to chemoradiation in a mixed cohort [ 33 ].…”
Section: Distal Esophagus or Gej Adenocarcinomamentioning
confidence: 99%
“…Although clinically significant, the study was underpowered for statistical significance [ 47 ]. Interestingly, NeoSCOPE ( n = 85) evaluated two neoadjuvant chemoradiation regimens (Oxaliplatin + Capecitabine + 45 Gy vs. Carboplatin + Paclitaxel + 45 Gy) with improved OS in the latter treatment group (HR 0.48, 95% CI 0.24–0.95, p = 0.035) [ 48 ]. Lastly, Dewitt et al evaluated a mixed cohort for treatment with intratumoral paclitaxel in conjunction with chemoradiation (cisplatin + 5-FU + 50.4 Gy) compared to chemoradiation with no improvement in OS [ 33 ].…”
Section: Distal Esophagus or Gej Adenocarcinomamentioning
confidence: 99%